2008
DOI: 10.1002/adfm.200800662
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Biomaterials for Regeneration

Abstract: Biomaterials play a pivotal role in regenerative medicine, which aims to regenerate and replace lost/ dysfunctional tissues or organs. Biomaterials (scaffolds) serve as temporary 3D substrates to guide neo tissue formation and organization. It is often beneficial for a scaffolding material to mimic the characteristics of extracellular matrix (ECM) at the nanometer scale and to induce certain natural developmental or/and wound healing processes for tissue regeneration applications. This article reviews the fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(168 citation statements)
references
References 106 publications
(142 reference statements)
1
167
0
Order By: Relevance
“…Nano-fibrous scaffolds can be obtained when the gelation of the polymer solution system occurs due to the crystallization of polymer-rich phase and solvent removal. Ma et al have done intensive studies on the fabrication of PLLA NF scaffolds by TIPS and their influence on cell morphology and function in bone tissue engineering (Woo et al, 2003;Hu et al, 2008;Smith et al, 2009;Wei and Ma, 2008). Even now, no one reported the application of PCL-b-PLLA scaffold with nano-fibrous structure fabricated by TIPS in cartilage tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-fibrous scaffolds can be obtained when the gelation of the polymer solution system occurs due to the crystallization of polymer-rich phase and solvent removal. Ma et al have done intensive studies on the fabrication of PLLA NF scaffolds by TIPS and their influence on cell morphology and function in bone tissue engineering (Woo et al, 2003;Hu et al, 2008;Smith et al, 2009;Wei and Ma, 2008). Even now, no one reported the application of PCL-b-PLLA scaffold with nano-fibrous structure fabricated by TIPS in cartilage tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nanoporous or nano-fibrous polymer matrices played a critical role in providing support and anchorage for cells, while maintaining chondrocyte phenotype and enhancing chondrocyte growth and matrix synthesis Li et al, 2006). The fabrication technologies used for scaffold fabrication in cartilage tissue engineering included electrospinning (Wise et al, 2009), particulate leaching combined with chemical etching Park et al, 2005) and 3-D printing techniques (Yen et al, 2009). L-L TIPS is an easy and effective technique to fabricate 3D nano-fibrous scaffolds (Ma, 2008;Zhang and Ma, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Human bones are made up of 35 % organic matter, mainly collagen type I, and 65 % inorganic substances, where calcium phosphate predominates. In view of this, beside the polymer forming the fibrous frame, advanced bone substitutes include hydroxyapatite, which strengthens the structural integrity of the substitute and enables good osteoconductivity and binding of the natural bone components on the substitute (30). In vitro studies have confirmed a high degree of osteoblast attachment and growth on nanofibers from chitosan and hydroxyapatite as well as a significantly increased mineralization as soon as in 15 days (31).…”
Section: Nanofibers As Advanced Bone Substitutesmentioning
confidence: 88%
“…Alignment of polymer backbone structures along fiber axes forms crystal domains [150][151][152], which have provided a foundation for optoelectronics such as nanofiber light sources with color tunability and waveguide capabilities and nanofiber lasers [39,146,148,. Biologically, hybrid nanofiber scaffolds have provided a cell niche conducive to improved attachment, proliferation, and cell differentiation [190][191][192][193][194][195][196][197][198], as well as targeted drug delivery carriers [198][199][200][201][202][203][204][205][206]. Filtration using ONFs [207] equipped with activated carbon has revealed adsorption of volatile organic compounds (VOCs) present in the air [208][209][210], and Scholten et al reported that adsorption and desorption of VOC by electrospun nanofibrous membranes (ENMs) were faster than that of conventional activated carbon [208].…”
Section: Organic Micro-and Nano-fiber Systemsmentioning
confidence: 99%